Professional High School (EPA.L.) As A Means Of Configuration And Exercise Of Internal Educational Policy (International Journal of Scientific Research and Management (IJSRM), 2016)
This research is innovative in the field of organization and administration of education in Greece because the issue has not been scientifically researched in EPA.L. Purpose of the research is to determine the views and perceptions of teachers’ while they exercise the educational policy of EPA.L. and to record their proposals and suggestions. The research was conducted with the use of semi-structured interview. Key findings of the research are that EPA.L. is necessary in the current difficult time, it need to stand on its own feet, it must find ways of saving resources and it should be supported by the local community.